3D SPH porous flow model for wave interaction with permeable structures. (June 2018) - Wen, Hongjie; Ren, Bing; Wang, Guoyu
Highlights: A 3D SPH porous flow model is developed to assess the hydrodynamic characteristics around the permeable coastal structures. The model is validated against other available numerical results and experimental data. The validated model is applied to study wave interaction with a detached shore-parallel breakwater of two layer porous media. The predicted 3D circular flows fields around the permeable shore-parallel breakwaters are analyzed. Abstract: A three-dimensional smoothed particle hydrodynamic (3D SPH) porous flow model for wave interaction with permeable structures is developed to assess the 3D effects around the coastal structures with complex geometrical boundaries. The Volume Averaged and Favre Averaged Navier-Stokes (VAFANS) equations along with the Sub Particle Scale (SPS) turbulence model are implemented as the governing equations to describe the fluid motion both inside and outside the permeable structure. The empirical frictional source terms are introduced to represent the resistance forces on the fluid flow induced by the solid skeleton of the porous structure. The permeable interface is treated as a transition zone and the porosity value changes continuously in this zone by using an interpolation algorithm over the background porosity points. The present model is validated by the available numerical results for dam-breaking wave impacting on a porous square prism and the experimental data for solitary wave interaction with a vertical porous breakwater. The validated model is then applied to investigate wave interaction with a detached shore-parallel breakwater of two layer porous media. The predicted 3D flow field inside and outside the permeable breakwater is analyzed. The spatial distributions of wave-induced current induced by wave breaking are also discussed.